The market potential of oil palm empty-fruit bunches particleboard as a furniture material - Ratnasingam, Jegatheswaran; Wagner, Karl (2009)
The study evaluated the consumer perceptions towards particleboard as a premier furniture material. The data for this study was collected from a questionnaire survey, completed by 500 buyers who attended the international furniture fairs in Malaysia in 2008. Correlation analysis showed that the success factors of particleboard as a furniture stock are primarily its low cost and environmental friendly status. Further, the study also revealed that the major advantages of particleboard made from oil palm empty-fruit bunch (EFB), a potential substitute for the conventional wood-based particleboard, are its comparatively lower cost and greater environmental friendliness. Since, particleboard-based furniture are perceived as being inexpensive and fragile, the choice of using particleboard in furniture manufacturing is driven primarily on cost, rather than performance. Therefore, the market potential of oil palm EFB particleboard is dependent on its comparative cost, which could increase market share if the material is available at a competitive price.